Assessment of mould growth in selected hospital : Air conditioning system aspect - Ali, Maisarah; Bamgpopa , Ibrahim Atanda (2010)
Moulds growth in indoor environments has been of concern in the built environments,particularly in the hospital environment. Several studies have shown direct correlation between the exposure to moulds growth and copious adverse health effects. The Air-Conditioning systems in the hospital environments are tasked to provide comfortable environmental conditions in order to facilitate the healing process and support diversemedical functions in hospitals. Ironically, Air-Conditioning systems are often implicated as source of moulds infestation. Malaysia does not have its own standard for hospitals’ Indoor Air Quality (IAQ). Therefore, the premises of this study is that, the assessment of cases of mould infestation in selected newly commissioned hospitalwith respect to their Air-Conditioning systems will be an endeavour to provide deeperinsight into the causes of this menace. The investigation was carried out using formulated assessment checklist for both the indoor space assessment and the air-conditioning system assessment respectively. 32Air Handling Unit (AHU) were inspected. The results of the investigations show condensation to be the predominant source of moisture for mould growth in all the case studies. While in some instances stagnation of air due to poor ventilation and high relative humidity were hypothesized as the causal factors. However, in some of the case studies, the results of the inspection carried out on some of the AHU, establishes the need for more “stringent” design, and operation & maintenance guidelines particularly for the hospital needs.